Microgreens: Functional Food for Nutrition and Dietary Diversification - Tania Seth; Gyan Prakash Mishra; Arup Chattopadhyay; Partha Deb Roy; Mridula Devi; Ankita Sahu; Sukanta Kumar Sarangi; Chaitrali Shashank Mhatre; Yvonne Angel Lyngdoh; Visalakshi Chandra; Harsh Kumar Dikshit; Ramakrishnan Madhavan Nair (Plants)
Microgreens are tender, edible seedlings harvested 7–21 days after germination containing a central stem, cotyledons, and true leaves. Known as a fresh, ready-to-eat functional food, they are mostly rich in vitamins, antioxidants, bioactive compounds, and minerals, with distinctive flavors, colors, and textures. These attributes make microgreens a valuable component in nutrition and health research. In countries like India, where low-income households spend 50–80% of their income on food, micronutrient deficiencies are common, particularly among women. Indian women, facing a double burden of malnutrition, experience both underweight (18.7%) and obesity (24.0%) issues, with 57% suffering from anemia. Women’s unique health requirements vary across life stages, from infancy to their elderly years, and they require diets rich in vitamins and minerals to ensure micronutrient adequacy. Microgreens, with their high nutrient density, hold promise in addressing these deficiencies. Fresh and processed microgreens based products can enhance food variety, nutritive value, and appeal. Rethinking agriculture and horticulture as tools to combat malnutrition and reduce the risk of non-communicable diseases (NCDs) is vital for achieving nutritional security and poverty reduction. This review compiles recent research on microgreens, focusing on their nutrient profiles, health benefits, suitable crops, substrates, seed density, growing methods, sensory characteristics, and applications as fresh and value-added products. It offers valuable insights into sustainable agriculture and the role of microgreens in enhancing human nutrition and health.